Medication Adherence in Pulmonary Tuburculosis Patients - Sulistiyono, Andi; Monika, Yasa; Nilyatii; Rosyidi, Muhammad Imron (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Medication adherence in patients with pulmonary Tuberculosis (TB) is a critical factor for treatment success and disease transmission prevention. This study aimed to describe the characteristics of patients and the patterns of medication adherence among pulmonary TB patients in three healthcare facilities in Indonesia, namely Puskesmas Permata Kecubung, Sukamara Regency; Puskesmas Tanah Kuning, Bulungan Regency; and RSUD Muhammad Zein, East Belitung Regency. A descriptive quantitative method with a survey design was used. The sample consisted of 60 patients, with 20 patients from each location, selected using accidental sampling. Data collection was conducted simultaneously on March 29, 2026. Data were collected using a medication adherence questionnaire and an observation sheet to record patient characteristics, including age, gender, and education level. The results showed that the majority of respondents were aged 30–50 years (48.3%), with an equal distribution of males and females (50% each), and most respondents had a secondary education level (45%). The findings on medication adherence indicated that most respondents were in the adherent category (45%), followed by moderately adherent (35%) and non-adherent (20%). Variation among locations revealed the highest adherence at RSUD Muhammad Zein (50%) and the lowest at Puskesmas Tanah Kuning (40%). In conclusion, medication adherence among pulmonary TB patients in the three healthcare facilities is still at a level that needs improvement. Therefore, continuous education, routine monitoring, and strengthening support from family and healthcare providers are required to enhance patient adherence to completing their treatment. These efforts are expected to improve therapy success and reduce TB transmission in the community.